The Impact of E-Commerce Development on Conventional Merchants’ Income (case study: Medan central market) - Eri Yanti Nasution (AIBPM Publisher, 2019)
The development of technology, buying and selling with conventional method or face to face method is an old habit that is starting to be abandoned by consumers. This is because ecommerce in Indonesia is growing rapidly. As of 2016 total online sales in Indonesia are around Rp 4.49 billion. The development of e-commerce will affect the existence of conventional sales. The study aims to analyze the impact of the development of e-commerce on the conventional merchants’ income. The data in this study are primary data by distributing questionnaires to clothing merchants’ in Medan central market. Data analysis methods used are simple regression analysis and sampling techniques using accidental sampling. The results showed that the development of e-commerce did not have an impact on conventional merchants’ income in Medan central market. This is caused conventional merchants’ having a strategy to survive in digital era.